Is it the plants we know that we use? Unraveling the determining factors of ethnobotanical knowledge in a rural community in Central Mexico - Beltrán, Leonardo; Gutierrez, Jesús; Flores, Gabriel; Saynes, Alfredo; Maldonado, Belinda; Blancas, José; Ortiz, Amanda (Ethnobiology and Conservation, 2022)
The knowledge and use of plant resources are constantly evolving. In this work, the socio-cultural and economic factors that influence the ethnobotanical knowledge of a mestizo community in Mexico were analyzed, and the correspondence of two cultural indices (use value vs. practical value) was determined to identify the magnitude of the significance and utility of each of the ethnofloristic resources. The study was carried out through semi-structured interviews with 44 local informants. Free lists were applied, and the indexes of use value and practical value were used to document the most culturally important plants.With an analysis of covariance (ANCOVA), the differences in botanical knowledge between genera and the effect of socioeconomic covariates on it were evaluated. 223 species were recorded in 54 botanical families and 86 genera, of which 48% were herbs and just over 60% of the total were recorded in homegardens. The Asteraceae family had the highest number of useful species followed by Fabaceae and Rosaceae. Of a total of 10 categories of use, medicinal, food and ornamental plants were the most representative. A weak correspondence was found between the cultural indices at the species level, but there was consistence at the level of use categories. The ANCOVA showed that there is no statistically significant difference between the genders and none of the covariates have a significant influence (p>0.05) on ethnobotanical knowledge. However, there was a consensus between men and women on the importance they give to medicinal and food plants.